The effect of 6-week hopping exercises program on joint position sense in athletes with functional ankle instability - Mohammad Karimizadeh Ardakani; Mohammad Hossein Alizade; Esmaeil Ebrahimi Takamjani (Vesnu Publications, 2013)
Introduction: The purpose of this study was to examine the effect of 6 weeks hopping exercises program on joint position sense in young male athletes with functional ankle instability. Materials and Methods: Thirty young male athletes with functional ankle instability (mean ± SD age; 22.16 ± 1.46 years, mean ± SD weight; 73.96 ± 11.50 kg, mean ± SD height; 180.95±8.24 cm, mean ± SD instability score; 20 ± 2.31) were participated in this study. They all read and signed the consent form. Participants were equally and randomly divided into two following groups: 1) hopping exercise, and 2) control. Reproduction of ankle joint angle was used to evaluate joint position sense before and just after exercise program. Descriptive statistic, paired sample t-test and Independent sample t-test were used to analyze the data. Level of significance was set at P < 0.05. Results: The results of the study showed that 6 weeks hopping exercise program had a significant decrease in average absolute error of the reproduction of ankle joint angle in inversion and plantar flexion (P < 0.05). Furthermore, reduce in absolute error of joint angle reproduction was observed more in inversion than plantar flexion. Conclusion: According to the results, young male athletes with functional ankle instability need specific joint position sense in many skills. So, it could be suggested to use these selected exercise in training and rehabilitation programs to improve joint stability during fast and rapid activities. Keywords: Hopping exercises, Joint position sense, Functional ankle instability, Young athlete